2008
DOI: 10.1203/pdr.0b013e31816bdf54
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Tissue-Engineered Cornea: Biomaterials and Culture Methods

Abstract: ABSTRACT:The field of corneal tissue engineering has made many strides in recent years. The challenges of engineering a biocompatible, mechanically stable, and optically transparent tissue are significant. To overcome these challenges, researchers have adopted two basic approaches: cell-based strategies for manipulating cells to create their own extracellular matrix, and scaffold-based strategies for providing strong and transparent matrices upon which to grow cells. Both strategies have met with some degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 57 publications
(59 reference statements)
1
66
0
1
Order By: Relevance
“…10 A fully functional TE cornea must be able to re-create the complex and unique arrangement of the ECM because the architecture of the corneal stroma affects the optical properties of the cornea. 17 Further, studies have found that the orientation of collagen fibers can affect cell behavior, such as adhesion and direction of proliferation. 18,19 Many tissue engineers use electrospinning to replicate the fibrous nanostructure of various ECMs.…”
mentioning
confidence: 99%
“…10 A fully functional TE cornea must be able to re-create the complex and unique arrangement of the ECM because the architecture of the corneal stroma affects the optical properties of the cornea. 17 Further, studies have found that the orientation of collagen fibers can affect cell behavior, such as adhesion and direction of proliferation. 18,19 Many tissue engineers use electrospinning to replicate the fibrous nanostructure of various ECMs.…”
mentioning
confidence: 99%
“…In order to meet the abovementioned design criteria, the tissue engineering structure must have the following essential characteristics [137]: (i) to stimulate the migration and proliferation of corneal epithelial cells for the formation of a functional corneal epithelium, (ii) to resist the intraocular pressure, and thus to prevent rupture, (iii) simulating the nanoscale fibrillary order of the corneal stroma to show a high degree of transparency (>90°C) and a refractive index comparable to that of the native cornea (3.8 MPa) [138] and the refractive index, (iv) transparency to support the maintenance of functional keratocytes to preserve and de novo collagen tissue synthesis, and (v) to compensate for and thereby prevent the swelling rate of the native cornea to preserve and distribute the water content [139].…”
Section: Cornea Tissue Engineeringmentioning
confidence: 99%
“…The next challenge is to ensure that these constructs show appropriate thickness, transparency, and strength in vivo. However, issues like cellular responses, wound healing, and inflammatory responses need to be studied in detail clinically before any conclusions can be drawn [6]. This paper highlights the new insights in the corneal endothelial cell culture and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation, culturing, and bioengineering have been studied to a limited extent, and further research is ongoing. Attempts have already been discussed in the literature for exploiting the power of native cells for the manufacturing of stroma-like extracellular matrix and for the production of cell sheets, whether it be the epithelium with amniotic membrane/fibrin or endothelial cells with intact basement membranes [6]. It has also been found that collagen-based engineered matrices support cell growth and demonstrate appropriate optical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%